Salicylate increased ascorbic acid levels and neuronal activity in the rat auditory cortex - Qingchuan Duan; Furong Ma; Jie Zhang (Wiley, 2019)
Abstract Importance Clinical observations have implied a central origin for tinnitus and potential therapeutic effects of ascorbic acid (AA); however, the detailed mechanisms remain undetermined. Objective To investigate changes in the AA levels and neural activity in the auditory cortex (AC) during salicylate‐induced tinnitus. Methods Rats were randomly divided into 3 groups: (1) saline group, which received an intraperitoneal saline injection; (2) SS group, which received an intraperitoneal sodium salicylate (SS) injection (350 mg/kg); and (3) SS+Lido group, which received an intraperitoneal SS injection (350 mg/kg) and lidocaine delivered to the AC by microdialysis. For each group, we firstly used an in vivo microdialysis technique to investigate the concentrations of AA in the AC; and secondly, we recorded the neural activity in the AC using a single‐unit recording technique. Results The AA concentration in the SS group significantly increased after SS injection, whereas that of the saline group did not change. The AA concentration in the SS+Lido group also showed an increasing trend but was significantly lower than that in the SS group. In the electrophysiological study, the spontaneous firing rate of the SS group was significantly higher than that of the saline group. In addition, the proportion of short interval discharges was also higher in the SS group than in the saline group. Both differences were reversed by lidocaine treatment. Interpretation Our data suggest that the elevation of AA levels in the AC may be related to increased neuronal activity, which may represent the mechanism underlying salicylate‐induced tinnitus.